Efficacy of Odontoid Screws in Acute Type II Odontoid Fractures - Mohamed AR AbdelFatah *; Abdelrahman El Gayar; Omar El Farouk Ahmed; Sameh Hefny (SVU - International Journal of Medical Sciences, 2024)
Background: Several surgical stabilization options are available for odontoid fractures; however, there is no consensus on the best option. Objectives: This study aimed to assess the efficacy of odontoid screws in acute type II odontoid fractures regarding bony fusion and alignment. Patients and methods: This cohort study retrospectively reviewed the medical records at our university hospitals from January 2015 to December 2020. We included the data of the patients who underwent odontoid screws for acute type II odontoid fractures. Patients with odontoid fractures type I on the Roy-Camille classification were excluded. A follow-up CT scan of the cervical spine one year after the operation was done to assess odontoid fusion and alignment. The statistical analyses were conducted using SPSS software version 21 (IBM Corp., Armonk, New York, USA). Results: Our study included 22 cases, 19 males (86.3%). Their average age was 25.9 +/- 4.7 years. There were no other associated cervical spine fractures in any patient. Preoperatively, 21 patients (95.45%) were grade E on the AIS, and one case (4.55%) was grade D. All the patients had an intact transverse ligament. A follow-up CT of the cervical spine after one year shows good bony fusion in 21 cases (95.5%) and a fibrous fusion in one case (4.5%). The odontoid processes were in good alignment in all cases. There were no broken screws. Conclusion: Odontoid screws appeared to be efficacious for the stability and fusion of acute odontoid fracture type II with good bony alignment.